Maternofetal outcome in obstructed labour in a tertiary care hospital - Rizvi, Syed Masuma; Gandotra, Nikita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Obstructed labour is still a major cause of maternal morbidity and mortality and adverse outcome of newborn in low income countries. It is the leading cause of hospitalization, comprising of 39% of all obstetric patients in developing countries. Objectives: To study frequency, causes outcome and complications of obstructed labour. Methods: 402 patients admitted with feature of obstructed labour were studied. Detailed history included sociodemographic factors, obstetric history, features of obstruction, intrapartum events were recorded. Condition of patients, mode of delivery, preoperative and postoperative complications, maternal and fetal outcomes was recorded. Results: A total of 23381 deliveries were conducted during one year, 402 cases of obstructed labour were found with incidence of 1.71%. 86.5 % of the patients were from rural areas and 78.1 % of patients were unbooked and73.3% patients were primigravida. The commonest cause of obstructed labour was cephalopelvic disproportion (55%) followed by Malposition (22.9%) and Malpresentation (17.9%). The commonest mode of delivery was cesarean section (83.8%). Instrumental deliveries were conducted in 10.5% of cases. Destructive procedures are discouraged in out set up. Rupture uterus was seen in 16 cases (4.16%) out of which repair was done in 11 cases and subtotal hysterectomy was performed in 5 patients. The common maternal complications were sepsis [pyrexia (15.1%), wound infections (12.8%), urinary tract infection (7%), abdominal distention (11.2%), postpartum hemorrhage (9.7%). Perinatal mortality was 107/402 (26.6%), live birth rate 316/402 (78.7%), still birth rate 86/402 (21.3%). Perinatal morbidity was most commonly due to birth asphyxia (28.8%), jaundice (16.9%), septicemia (14.75%), meconium aspiration syndrome (9.9%). Conclusions: Obstructed labour is a preventable condition prevalent in developing countries. Improving nutrition, antenatal care, early diagnosis and timely intervention may result in decrease in incidence of morbidity and mortality.